SELECTION OF AN OPTIMAL HEALTH-RELATED QUALITY-OF-LIFE QUESTIONNAIRE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - L. D. Vorobyeva; E. A. Aseeva; S. K. Solovyev; S. I. Glukhova (Научно-практическая ревматология)
Objective: to provide a rationale for selecting a health-related quality of life (HRQOL) questionnaire in patients with systemic lupus erythematosus (SLE).Subjects and methods. The investigation enrolled 328 patients (298 women and 30 men) with documented SLE who met the 2012 Systemic Lupus International Collaborating Clinic (SLICC) criteria. The patients’ mean age was 34.4±11.5 years; the disease duration was 106.3±97.9 months. All the patients underwent an assessment of the current activity of the disease by the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) and organ damages by the SLICC damage index (DI). HRQOL was assessed using the 36-item Short-Form Health Survey (SF-36) and Lupus Quality of Life (LupusQol) questionnaires, which had been filled out by the patients.Results and discussion. The assessment using both questionnaires revealed a considerable decline in HRQOL for all domains. There was a highly significant correlation among the comparable SF-36 and LupusQoL domains: «Physical Health» and «Physical Functioning» (r=0.8), «Emotional Health» and «Psychological Health» (r=0.4), «Pain» (r=-0.3), «Fatigue», and «Vitality» (r=-0.7). Disease activity has a statistically significant effect on «Planning» (p<0.0004), «Intimate Relationships» (p<0.003), «Dependence on Other People» (p<0.03), and «Body Image» (p<0.007), which cannot be assessed using the 36-item Short-Form Health Survey (SF-36) questionnaire, but which are contained only in the LupusQol questionnaire. Both SF-36 and LupusQol equally reflect HRQOL changes in the presence of irreversible organ damages. Since lesions of the joints, skin and nervous system significantly affect domains, such as «Planning», «Intimate Relationships», «Dependence on Other People», and «Body Image» in SLE patients, LupusQol is the choice of questionnaire when these changes are present. When conducting scientific and clinical research, it is advisable to use both questionnaires for greater objectification of data. When conducting researches and clinical trials, it is advisable to use both questionnaires for greater data objectification.